Strategi integrasi nilai islam dan pancasila melalui kurikulum integratif dan budaya akademik di uin malang - al-ghifari, achmad jeffry (Maliki Interdisciplinary Journal, 2026)
This research aims to examine the integration of Islamic values and Pancasila in the development of science at UIN Maulana Malik Ibrahim Malang. Using a descriptive qualitative approach with pedagogical and sociological perspectives, this study explores the institution's efforts to eliminate the dichotomy between religious and general sciences. Data were collected through observations and purposive interviews with various elements of the university's educational system. The results indicate that integration is carried out systematically through an integrative curriculum, enhancing lecturer competence as moral role models, and strengthening a religious and nationalistic academic culture. Islamic values as a spiritual foundation and Pancasila as a national basis converge on the principles of divinity and humanity. Despite facing challenges such as cognitive dominance and the currents of globalization, this implementation is proven to contribute to forming student characters that balance spiritual depth and professional maturity. The study concludes that continuous strengthening of integration is essential to produce graduates who are not only academically bright but also possess solid moral integrity.